2018
DOI: 10.1126/science.aaq0179
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed and portable nucleic acid detection platform with Cas13, Cas12a, and Csm6

Abstract: Rapid detection of nucleic acids is integral for clinical diagnostics and biotechnological applications. We recently developed a platform termed SHERLOCK (Specific High Sensitivity Enzymatic Reporter UnLOCKing) that combines isothermal pre-amplification with Cas13 to detect single molecules of RNA or DNA. Through characterization of CRISPR enzymology and application development, we report here four advances integrated into SHERLOCKv2: 1) 4-channel single reaction multiplexing using orthogonal CRISPR enzymes; 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
2,055
3
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,850 publications
(2,185 citation statements)
references
References 28 publications
14
2,055
3
11
Order By: Relevance
“…This HEPN-activated conformation of Cas13 is a general nuclease, which is capable of cleaving either the RNA molecule that it was activated by ( cis cleavage), or any other RNA molecule that it happens to encounter ( trans / collateral cleavage). All Cas13 proteins characterized to date exhibit these behaviors (Abudayyeh et al, 2016; East-Seletsky et al, 2016; East-Seletsky et al, 2017; Gootenberg et al, 2018; Gootenberg et al, 2017; Konermann et al, 2018; Smargon et al, 2017; Yan et al, 2018). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This HEPN-activated conformation of Cas13 is a general nuclease, which is capable of cleaving either the RNA molecule that it was activated by ( cis cleavage), or any other RNA molecule that it happens to encounter ( trans / collateral cleavage). All Cas13 proteins characterized to date exhibit these behaviors (Abudayyeh et al, 2016; East-Seletsky et al, 2016; East-Seletsky et al, 2017; Gootenberg et al, 2018; Gootenberg et al, 2017; Konermann et al, 2018; Smargon et al, 2017; Yan et al, 2018). …”
Section: Introductionmentioning
confidence: 99%
“…The RNA-activated RNA cleavage behavior of Cas13 provides a mechanism for RNA detection and diagnostic applications (East-Seletsky et al, 2016; Gootenberg et al, 2018; Gootenberg et al, 2017), as well as RNA-targeting in heterologous systems (Abudayyeh et al, 2017; Aman et al, 2018; Cox et al, 2017; Konermann et al, 2018). Versions of Cas13 where the HEPN-domains have been catalytically inactivated (Abudayyeh et al, 2016; East-Seletsky et al, 2016; Konermann et al, 2018; Smargon et al, 2017; Yan et al, 2018) (deactivated Cas13; dCas13) have shown to be useful as programmable RNA binding proteins for RNA imaging (Abudayyeh et al, 2017), RNA editing (Cox et al, 2017) and regulating specific transcripts RNA in other ways (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Two papers also published in Science on 15 February describe how CRISPR can be used to detect disease-causing viruses 2,3 .…”
Section: By H E I D I L E D F O R Dmentioning
confidence: 99%
“…Hybridization-based methods include dynamic allele-specific hybridization, molecular beacons, SNP arrays and a probes-on-carrier DNA chip [18–21]. Enzyme-based methods include restriction fragment length polymorphism (RFLP) and cleaved amplified polymorphic sequence (CAPS) assay, invader assay, primer extension assay, TaqMan assay, oligonucleotide ligation assay (OLA), Surveyor nuclease assay, T7 endonuclease I (T7EI) cleavage assay, PCR/RNP assay, and specific high-sensitivity enzymatic reporter unlocking (SHERLOCK) assay [22,23]. The conformation- or melting temperature-based methods include single-strand conformation polymorphism assay, heteroduplex assay (HDA) or heteroduplex mobility assay (HMA), denaturing and temperature gradient gel electrophoresis (DGGE and TGGE) assay, denaturing high-performance liquid chromatography (DHPLC), high-resolution melting analysis (HRMA), and MutS binding assay [24–27].…”
mentioning
confidence: 99%